Microfluidic Devices: Simple 3D Printed Scaffold‐Removal Method for the Fabrication of Intricate Microfluidic Devices (Adv. Sci. 9/2015). Issue 9 (September 2015) - Saggiomo, Vittorio; Velders, Aldrik H.
<x xml:space="preserve">Abstract</x> ESCARGOT (Embedded SCAffold RemovinG Open Technology) is a novel and simple methodology for the manufacturing of complex microfluidic devices in a single block of polydimethylsiloxane, developed by V. Saggiomo and A. H. Velders in article number 1500125. Dissolvable scaffolds are used for the creation of microfluidic channels without the use of clean rooms, and integration of external elements directly in the microfluidic device is shown to be easy.